ANALYSIS OF DECISION MAKING STRATEGIES IN RESOLVING ENERGY DEFICIT IN PARANG ISLAND, GENTING ISLAND AND NYAMUK ISLAND Case Study on PT PLN (Persero) Central Java and D.I Yogyakarta Distribution Unit - Syah Yogta Wipogso; Mahfudz (RADJA PUBLIKA, 2025)
Energy deficit is one of the problems that often occurs in remote areas, such as in Parang Island, Genting and Nyamuk. This requires the best solution in overcoming existing problems. Decision making is a process in which various options are selected to get maximum results. This process includes identifying needs or problems, collecting relevant data, assessing existing alternatives and selecting the most appropriate and suitable solution. Effective decision making will have a good influence on the company in increasing efficiency, overcoming problems and achieving targets. Qualitative research with case study as the research design was used to develop the case. Semi-structured interviews with 4 informants who had been selected through purposive sampling were conducted to collect research data. The interview results were analyzed and processed using triangulation techniques, and member checking was conducted to ensure credibility and trustworthiness in the research. This study aims to determine the best decision-making in overcoming the problem of electricity deficit. The results of the study indicate that the criteria considered are energy independence, cost efficiency, and an effective management system, adjusted to geographical conditions to create a stable and reliable electricity supply for the community. Solar Power Plants (PLTS) are the most appropriate choice as a utilization of new renewable energy sources through efficient and environmentally friendly management. Optimizing decision-making requires effective collaboration between stakeholders from the regions and centers, to involving the community and experts to ensure success in overcoming the problem of electricity deficit on Parang Island, Genting Island and Nyamuk Island.